Impact of the war in Ukraine on the epidemic situation with tuberculosis as a challenge for the world community - I.O. Novozhylova (Civic Union "Communicable Diseases Intensive Care Association", 2024)
ABSTRACT. Since wars have a powerful impact on public health and the health care system, the purpose of this analysis of available scientific sources is to examine the impact of the war in Ukraine on the state of the tuberculosis problem in the world. The review presents the epidemic situation with tuberculosis before the start of the war in Ukraine. It is especially emphasized that Ukraine ranks second in Europe in terms of the burden of HIV infection / acquired immunodeficiency syndrome and fifth in the world in terms of the number of confirmed cases of tuberculosis with multiple drug resistance. It is emphasized that the COVID-19 pandemic has seriously undermined the progress achieved in the fight against tuberculosis worldwide. The expected worsening of the epidemic situation with tuberculosis in Ukraine due to the war and its impact on the world health care systems are substantiated, and attention is focused on the urgent need to coordinate the efforts of the world community to overcome such a challenge. Problematic issues regarding the readiness of international health care systems to combat tuberculosis in the conditions of war in Ukraine are analyzed. Studying the current state of the problem "tuberculosis and the war in Ukraine" will allow us to act in the direction of reducing the negative impact of the war on the epidemic situation with tuberculosis both in Ukraine and partially in the whole world.